The complete chloroplast genome of the medicinal plant Paederia foetida L. Issue 7 (3rd July 2022) - Wang, Wei; Xu, Tao; Song, Xiangwen; Chen, Cunwu; Liu, Dong; Han, Bangxing; Yi, Shanyong
Abstract: Paederia foetida L. belonging to Rubiaceae family is a perennial medicinal herb widely distributed in India and China. The first complete chloroplast genome sequence of P. foetida was assembled and characterized in this study. The total chloroplast genome was 153, 591 bp in length with 37.74% GC content, composed of a large single-copy (LSC) region of 83, 677 bp, a small single-copy (SSC) region of 16, 888 bp and a pair of inverted repeat (IR) regions of 26, 513 bp. The whole chloroplast genome encoded 133 genes, including 88 protein-coding genes, 37 tRNA genes and 8 rRNA genes. Phylogenetic analysis of 30 chloroplast genomes strongly suggested that P. foetida was closely related to P. scandens.